Real-world data on the dose-related effect of arsenic trioxide in the relapse of acute promyelocytic leukemia - Gong, Sha (Mol Clin Oncol, 2020)
Acute promyelocytic leukemia (APL) has become a highly curable disease with all-trans retinoic acid-based regimens. However, following the administration of arsenic trioxide (ATO), the relapse rate remains at 1-10%. It is not known whether the dosage of ATO is associated with the relapse rate in real-world settings. According to 2019 National Comprehensive Cancer Network guidelines, the recommended cumulative ATO dosage in post-remission therapy is 7.95-12 mg/kg in APL. In the current study, 112 patients with newly diagnosed APL receiving a combination of all-trans retinoic acid, anthracycline-based chemotherapy and different dosages of ATO for variable courses, were divided into the high-dose (ATO dosage, ≥12 mg/kg) and low-dose groups (ATO dosage, <12 mg/kg). Relapse risk factors were analyzed by multiple factor analysis. The relationship between relapse rate and ATO dosage in post-remission was elucidated by determining the 4-year cumulative incidence of relapse (CIR). Based on the ATO dosage in post-remission therapy, 72 (64.3%) patients were in the low-dose group and 40 (35.7%) were in the high-dose group. An increased ATO dosage was demonstrated to be an independent protective factor in terms of probability of relapse (P=0.004). With a median follow-up time of 53 months, the 4-year CIR was 16.7% in the low-dose group and 0% in the high-dose group, respectively (P=0.008). No patient relapsed when administered an ATO dosage >6 mg/kg. In conclusion, the relapse rate of APL was significantly associated with ATO dosage in post-remission therapy. An increased ATO dosage may serve as a protective factor of relapse. ATO dosage should therefore reach up to 12 mg/kg, with consideration to reduce the dosage in the future.